NaSS: system simulation of inland waterways. (1st January 2012) - Rogers, Cory M.; Hofseth, Keith D.
The Navigation System Simulation (NaSS) suite is composed of two primary applications: a Monte Carlo simulation model of vessel movements on an inland waterway system and a data processing and analysis tool for mining of historical data. NaSS was designed to answer potential questions relating to a waterway system under examination, for example: What is the overall system performance of a waterway under different operating, demand load and reliability conditions? How effective are alternative lockage polices at reducing delays and costs? How does any single improvement affect delays at other locks? This paper focuses on the simulation component called BasinSym.